Creativity behavior of librarians in Nigeria’s federal universities Ogunmodede Thomas Ayinla1 and Popoola Sunday - Olanrewaju (IJoLIS, 2023)
Purpose: This study examined the behavior of librarians in Nigeria’s federal universities with regards to their creativity. Design/ Methodology/ Approach: The population of 654 librarians was completely counted and a survey study design of the correlational type was used to elicit data. The tool for gathering data was a questionnaire. A response rate of 79.2% was achieved with 518 respondents who returned the data collecting instrument. At a significance level of 0.05, descriptive and inferential statistics were used to analyze the results.